Kesediaan Membayar (Willingness To Pay) Beras Organik di Kabupaten Banyumas dan Faktor Yang Mempengaruhinya - Niken Hapsari Arimurti; Kusmantoro Edy Sularso; Anny Hartati (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2021)
The objectives of this study are: (1) to identify the characteristics of organic rice consumers in Banyumas Regency, (2) to determine the maximum average price for organic rice that consumers in Banyumas Regency are willing to pay, and (3) to analyze and find out factors underlying the consumers’ willingness to pay for organic rice. This research was conducted in Banyumas Regency by interviewing 68 respondents who were selected using the snowball sampling method. Data is analyzed using descriptive analysis, contingent valuation method (CVM), and logistic regression analysis. The study indicates that the characteristics of organic rice consumers who are willing to pay more for organic rice in Banyumas Regency are mostly aged 36 to 55 years, having an undergraduate degree, working as civil servants, and having an income level of Rp 3.000.001 to Rp 6.000.000 with 1-4 family members. The maximum price for organic rice that consumers in Banyumas Regency are willing to pay is Rp18.346 per kilogram. Factors underlying the willingness to pay for organic rice are income, length of consumption, and consumers’ perception of organic rice quality.